The Effects of Red Cell Transfusion Donor Age on Nosocomial Infection among Trauma Patients - Loftus, Tyler J. (Am J Surg, 2017)
BACKGROUND: We hypothesized that packed red blood cell (PRBC) transfusions from older donors would be associated with fewer nosocomial infections among trauma patients. METHODS: We performed a four-year retrospective analysis of 264 consecutive adult trauma patients who received ≥1 PRBC transfusion during admission. The capacity of donor age to predict nosocomial infection was assessed by logistic regression. RESULTS: Thirty-three percent of all patients developed a nosocomial infection. Donor age was significantly higher among patients with nosocomial infection (40.3 vs. 37.6 years, p = 0.035), and the incidence of infection was directly proportional to donor age. The association between donor age and infection was strongest among recipients age ≥60 years, and was significant on multivariate regression for this cohort (OR 1.07 (95% CI 1.01–1.13), p = 0.024). CONCLUSIONS: Among trauma patients receiving PRBC transfusions, blood from older donors may be associated with increased risk for nosocomial infection.